A SYSTEMATIC LITERATURE REVIEW ON SOCIAL EXCHANGE THEORY (2020-2024) - Minerva Polina; Sambas Ade Kesuma (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Social Exchange Theory is an important foundation for explaining relationships and interactions between humans. This study aims to examine how this theory has been used, explained, and developed by researchers over the past five years, from 2020 to 2024. This study was conducted using the Systematic Literature Review (SLR) method, analyzing various articles published in reputable journals such as Scopus and Google Scholar. Twenty articles were used in this study. The analysis shows that social exchange theory has undergone a shift in its perspective, from initially emphasizing economic exchange and rational logic to now focusing more on psychology, moral values, and humanism. Throughout its development, this theory has not only explained relationships between individuals and organizations but also encompassed digital relationships and focused on sustainability. Concepts such as trust, reciprocity, fairness, and sustainability have become key elements that indicate the direction of this theory's development. Thus, Social Exchange Theory is now considered not merely a theory of reciprocity but rather a general framework for understanding the meaning and trust that connect people in various social relationships.